Emotional Intelligence, Empathy, Self-Esteem, and Life Satisfaction in Spanish Adolescents: Regression vs. QCA Models - Guasp Coll, Marian; Navarro-Mateu, Diego; Giménez-Espert, María Del Carmen; Prado-Gascó, Vicente Javier (Frontiers in Psychology, 2020)
Adolescence is a complex period, in which the individual is subject to profound emotional, physical and psychological changes. Healthy development during adolescence is crucial for future positive development, self-esteem and life satisfaction, are fundamental. The importance of sociodemographic variables (sex and age), empathy and emotional intelligence on self-esteem and life satisfaction were studied, comparing complementary methodologies, regression models and fuzzy-set qualitative comparative analysis models (fsQCA). This is a cross-sectional design in a convenience sample of 991 adolescents (528 females, 53.3%; aged between 12 and 19 years; M=14.01, SD=1.40) from Spanish schools. Data were collected using the Rosenberg Self-Esteem Scale (RSES), the Satisfaction With Life Scale (SWLS), the Basic Empathy Scale (BES) and Trait Meta-Mood Scale (TMMS24). The results of the regression models suggest that cognitive empathy, emotional clarity and emotional repair are the main predictor variables for self-esteem. Meanwhile, the results of the fsQCA suggest that being older and low levels of cognitive empathy, emotional clarity and emotional repair predict higher levels of self-esteem. On the other hand, life satisfaction in regression models is significantly predicted by the emotional clarity and emotional repair dimensions of the TMMS24 and self-esteem. Meanwhile, in the prediction of life satisfaction, the results of the fsQCA suggest, the most important interactions were high emotional clarity, emotional repair, and low self-esteem. As research has already shown, promoting empathy and EI, leads to higher levels of self- esteem and life satisfaction.